ANALISIS SUMBER PENDAPATAN DAN ALTERNATIF PENDANAAN UNIVERSITAS CAMBRIDGE: PERSPEKTIF MANAJEMEN PEMBIAYAAN PENDIDIKAN ISLAM - Arina Mana Sikana; Al Qony Puspasary; Muhammad Munadi (STKIP Pesisir Selatan, 2026)
Objective: This study analyzes the University of Cambridge's revenue management model and alternative funding, identifying implications for Islamic Education Financing Management (MPI) in Indonesia. It examines structural strengths and weaknesses of Cambridge's revenue model, including persistent operating deficits and ethical issues in endowment investment. Methods: This qualitative library research uses primary data from Cambridge's annual reports (2023-2025), CUP&A, CUEF, and Cambridge Enterprise publications. Secondary data include indexed journal articles (Sinta/Scopus), MPI textbooks, and trusted media. Data collection uses documentation; analysis uses descriptive-qualitative content analysis. Results: Cambridge's revenue model is highly diversified: international student fees (£191.7 million), CUP&A (>£1 billion), CUEF (£4.2 billion endowment), and Cambridge Enterprise. However, Cambridge experiences persistent operating deficits (£8–100 million) with staff costs reaching 58% of revenue. Ethical issues arise from endowment investment in arms companies. Novelty: This research offers a critical MPI perspective on the Western endowment model, identifying Islamic alternatives such as cash waqf-ijarah, educational zakat, and qardhul hasan as more equitable and ethical sustainable funding models.